Наукова картина як інтегральна модель пізнання світу - Кримець, Оксана Михайлівна (Національный університет біоресурсів і природокористування України, 2018)
Розглянуто актуальну проблему формування наукової картини світу як моделі пізнання, що поєднує й систематизує різні галузі – природничу, технічну, гуманітарну. За мету взято аналіз процесів реінтеграції наукових знань різних галузей, завдання – з'ясувати шляхи появи спеціальних назв техніки в результаті переосмислення значень термінів інших наукових сфер, відстежити особливості зміни семантичних структур вихідного та похідного термінів. Застосовано аналітико-описовий метод для розгляду кожної термінологічної одиниці в структурному та семантичному аспектах, для вивчення плану змісту термінів залучено методи дефініційного аналізу. Досліджено термінотворчу роль метафори як особливого засобу мислення в процесі пошуку нового спеціального найменування. Доведено, що терміни техніки утворюються внаслідок переосмислення спеціальних назв анатомії, ботаніки, хімії, міфології та інших наук, результатом перетворень є зміна спеціалізації вихідних значень, семної структури на денотативно-сигніфікативному рівні, найпоширенішою є метафора, що ґрунтується на схожості функції, зовнішнього вигляду, ознак порівнюваних об'єктів. Основні положення розвідки співвідносяться із результатами досліджень українських термінознавців (О. Винник, Л. Малевич, Т. Панько, Т. Петрова). Перспективним напрямом подальшої розвідки визначено дослідження шляхів метафоризації спеціальної лексики на матеріалі терміносистем інших наук, вивчення особливостей творення українських термінів, що репрезентують національну наукову картину світу.

The given article is devoted to the research of the scientific worldview as an integrated model of the world cognition which unites and systemizes different fields, namely scientific, technical and humanitarian ones. The purpose and the task of the article are to study the processes of scientific knowledge reintegration in different fields, the ways of special names introduction for technique as a result of the meaning reinterpretation of terms in other scientific fields. The analytical and descriptive met hod is used in the research to study every terminological unite in its semantic and structural aspects. The methods of definitive analyses are used to generalize and classify lingual facts, study of Ukrainian terms subject-matter plan, and precise their semantic structure. A review of scientific works is presented. It is found out that the scientific worldview is considered as a rational model of the world cognition formed by means of connection of certain phenomena into the whole in the process of the development of the science; it also gives the overall picture of the Universe and forms universal scientific knowledge. The general scientific worldview contains the idea of both the development of insentient substance and the biological and social revolution, that is, knowledge of various branches is integrated and intersected in the process of scientific knowledge, as well as in search of successful names of new concepts, and existing terms serve as the basis to name specific concepts in completely different fields. Scientific worldview is considered as a research program which defines the strategy of scientific cognition, and also provides the objectivization of scientific knowledge – its relation with the object researched and the incorporation in a correspondent culture. A special role in the research process belongs to the heuristic function of the scientific worldview, which acts as an algorithm that directs the formation of empirical facts. One of the ways of new scientific knowledge formation and, accordingly new terms, is researched: it is the scientific knowledge reintegration in different fields. As the consequence special technical names emerge in the result of a metaphorical reinterpretation of the meanings of the terms of distant and close scientific fields. The essence of metaphorical reinterpretation lies in the establishment of a new content of knowledge, which is achieved by conditional identification of the semantic fields of various specific scientific worldviews. In particular, technical terms swivel, diaphragm, pulp, fibers are formed by means of metaphorizing the special names of anatomy. Such technical terms as photosynthesis (botany), thermoregulation (physiology), virus (bacteriology), panel (geodesy), cyclone (meteorology), inhibition (chemistry), which have both general (thermoregulation, cyclone) and sector-specific (photosynthesis, virus, panel) features are formed by means of specific vocabulary of other scientific fields. Specific terms of technique can emerge as a result of reterminologisation of humanity science terms, in particular linguistics and mythology (metaphor, daemons). A complex process of metaphorisation which defines the inner development of lexical and semantic development is analyzed. The formation of technical terms is accompanied by semantic modifications, as well as by the changes of denotative and syllogistic correlation of original and derivative meanings. In a semantic structure, the meaning of the original term in the process of metaphorical reinterpretation is actualized and differential semes become motivating, or, vice versa, implicit seme motivator in the structure of the initial meaning can become differentiated in the structure of the derivative meaning. When creating technical terms, the process of lexical-semantic structures changing of the original terms occur; in particular, there is the transition from abstract to specific and, accordingly, there is the formation of a specific logical meaning structure. In some cases, one can also see the opposite process – the transition from a specific meaning to an abstract one by means of the denotative seme annihilation and the formation of an abstract and logical structure. For example, the terms photosynthesis, thermoregulation, inhibition in both the fields of science, and in technique denote processes, and therefore they express abstract concepts, so the term panel in the field of geodesy and technology denotes a specific concept. The interference from abstract to specific and, consequently, the formation of a specific logical structure, has occurred in the process of metaphorizing of the term cyclone, which in meteorology means "edding motion of the atmosphere with a decrease in air pressure from the periphery to the center of the vertiginous current...", and in the technique it is "a device for air purification". The process of interference from specific to abstract can be demonstrated in such an example: the virus is 1. Bacterium, noe of the smallest microorganisms causing infectious disease. 2. A program that can join other computer programs and cause crashes in their work. Newly-formed names express either sector-specific or general technical terms, which are used in many technical sub-sectors. In some cases, the term has several general technical meanings and one sector-specific (diaphragm). The reason for metaphorization is the similarity of features or functions of comparable concepts. Features on the basis of which the metaphor interference occurs are characterized. The functional similarity metaphor is the most common as the principle of action is the main category of technique. The metaphor which is based on the similarity of outer appearance and features of the objects compared is also common. It has several factors: functional and outer likeness, and outer likeness and a feature. It is proved that the terms of technique are formed as a result of reinterpretation of the special names of other scientific spheres of human activity, that is, the re-integration of the terms of different, sometimes quite remote, spheres occur. Scientific metaphor in the process of reinterpretation of the original term acts as a model, serves as a guide in finding a successful name, brings together remote scientific fields, thereby demonstrating the consistancy, integrality, and integrity of the scientific worldview.
Scientific worldview as an integrated model of the world cognition
Keywords: технічна терміносистема; загальнотехнічний термін; вузькогалузевий термін; метафора; сема-мотиватор; ядерна сема; диференційна сема; technical terminology system; general technical term; narrow-branch term; metaphor; motivator sem; nuclear sem; differential sem